RPA de Baixo Custo e SIG Aplicados ao Manejo de Floresta Ombrófila Mista Montana - Teleginski, Evandro (2018)
Considering that the Araucaria Forest presents only a small fraction of what was already at the beginning of colonization and that these fragments are under great pressure by the agricultural sector, there is a need for studies to enable sustainable management. The importance of the legal forest reserve as well as the environmental services provided by it is well-known, but the rural owner cannot afford the conservation and preservation burden individually. The Brazilian Forest Code provides only quantitatively the minimum legal reserve limit, but does not require parameters of quality and variability of species, since the continental dimensions of the country and great heterogeneity of the biomes would not allow the synthesis in a single law. In view of this complex scenario, it is necessary to have in-depth knowledge of the dynamics of the forest for better decision making aiming at the sustainability of the forest, respecting its capacity to sustain. With the advancement of information technology, satellite navigation, digital photogrammetry and geographical information systems, operational solutions have emerged at relatively low costs for the determination of attributes at the individual level. Therefore, this study aimed to use a system of high resolution geographic information and images obtained by unmanned aerial vehicle (UAV) for the diagnosis, monitoring and inventory of Araucaria angustifolia and Hovenia dulcis, in order to generate direct or indirect data of well - how to generate maps to support preextracted forest inventories. The study was carried out in the Center-South region of Paraná in private remnants of the Araucaria Forest. The census of the trees was carried out and then they were spatialized in a system of geographical coordinates, overlapping them in the UAV images. The crowns of the Araucarias were vectorized in order to obtain their respective areas for later correlation with the Diameter at the Height of the Chest - DAP and with the volumes. Also, flyovers with UAV were carried out in an area infested by Hovenia dulcis, the first one in July 2017, when H. dulcis did not present foliage, and in September 2017, shortly after the leaves were issued. This study demonstrated that low-cost aerial photogrammetry has potential to support the diagnosis of forest remnants and may reduce operating costs of forest inventory activities by obtaining preliminary information.